Self-similarity and multiwavelets in higher dimension - Cabrelli, Carlos A, 1949- (Memoirs of the American Mathematical Society, 2004)
Introduction Matrices, tiles, and the joint spectral radius Generalized self-similarity and the refinement equation Multiresolution analysis Examples Bibliography Appendix A. Index of symbols.